PERLINDUNGAN HUKUM TERHADAP KONSULTAN DALAM KONTRAK KERJA DENGAN PEMERINTAH STUDI PADA PT. MEGA SURYA KONSULTAN DI PANGKALAN BUN KALIMANTAN TENGAH - DENNY PURNAMA, ST NIM. A212141094, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis discusses the legal protection of the employment contract with the consultant in a government study on PT. mega solar consultant in Central Kalimantan bun base. of the results of this thesis can be concluded that the patterns that occur within the legal relationship between the employment contract consultant pt. mega solar consultant with the local government of West Kotawaringin the department of agriculture and animal husbandry with the agreement of infrastructure provision of appropriate agricultural technology plantation technical planning work the farm road to the agreement or contract to carry out construction work packages. Obstacles faced to give legal protection to consultants in the employment agreement with the government of West Kotawaringin namely the absence of legal protection against the consultants in carrying out consultancy in order to provide legal certainty to the consultants who are working, there are some clauses that incriminating consultants in carrying out the consultation include: termination contracts and termination of contracts, fines and restitution, as well as force majeure, contract work should be done so as to bring justice to each of the parties in a balanced way, including the existence of legislation specifically governing consulting services, thus providing legal certainty in doing employment and protection of consulting services. Contract clauses which provide benefits to the consultant in the implementation and completion of the employment contract, including the extended time of work, cooperation between providers with sub providers, the clause of the contract price, the peace clause in the employment contract, and the peace clause in the employment contract. Recommendations to shift the pattern of legal relations governed by the contract between the parties with the other parties to the agreements made in order to warrant the presence of an engagement on both sides. For the creation of legislation that specifically regulates the Consulting Services performed by the Consultant in order to provide legal certainty and legal protection in their work. In order for the inclusion of a clause in the contract between the Regional Government Kotawaringin by the Company that provides Consulting Services conducted in a2fair and balanced so as to produce an employment contract in accordance with the expectations of both parties.Keywords: Legal Protection, Against, Consultant, In, Work Contract.ABSTRAKTesis ini membahas perlindungan hukum terhadap konsultan dalam kontrak kerja dengan pemerintah studi pada PT. mega surya konsultan di pangkalan bun kalimantan tengah. dari hasil penelitian tesis ini diperoleh kesimpulan bahwa pola-pola hubungan hukum yang terjadi didalam kontrak kerja antara konsultan pt. mega surya konsultan dengan pemerintah daerah kabupaten kotawaringin barat dinas pertanian dan peternakan yakni dengan surat perjanjian pengadaan sarana prasarana tekhnologi pertanian perkebunan tepat guna pekerjaan perencanaan teknis jalan usaha tani yakni dengan surat perjanjian atau kontrak untuk melaksanakan paket pekerjaan jasa konstruksi. Kendala yang dihadapi untuk memberikan perlindungan hukum kepada konsultan dalam perjanjian kontrak kerja dengan pemerintah kabupaten kotawaringin barat yaitu belum adanya payung hukum terhadap konsultan dalam melaksanakan konsultansi dalam rangka memberikan kepastian hukum pada konsultan yang bekerja, adanya beberapa klausa yang memberatkan konsultan dalam melaksanakan konsultansi diantaranya : penghentian kontrak dan pemutusan kontrak, denda dan ganti rugi, serta keadaan kahar, Kontrak kerja yang seharusnya dilakukan sehingga memberikan keadilan kepada masing-masing pihak secara seimbang, diantaranya adanya peraturan perundang-undangan yang khusus mengatur mengenai jasa konsultansi, sehingga memberikan asas kepastian hukum dalam melakukan pekerjaan dan perlindungan terhadap jasa konsultansi. Klausa kontrak yang memberikan keuntungan kepada pihak konsultan dalam pelaksanaan dan penyelesaian kontrak kerja, diantaranya perpanjangan waktu pelaksanaan kerja, kerjasama antara penyedia dengan sub penyedia, adanya klausa harga kontrak, klausa perdamaian dalam kontrak kerja, dan klausa perdamaian dalam kontrak kerja. Rekomendasi agar pola hubungan hukum diatur melalui kontrak kerja antara satu pihak dengan pihak lainnya dilakukan dengan perjanjian kerja guna manjamin adanya suatu perikatan pada kedua belah pihak. Agar dibentuk Peraturan Perundang-undangan yang khusus mengatur mengenai Jasa Konsultansi yang dilakukan oleh Konsultan sehingga dapat memberikan kepastian hukum dan perlindungan hukum dalam melakukan pekerjaannya. Supaya dalam pencantuman klausa kontrak kerja antara pihak Pemerintah Daerah Kabupaten Kotawaringin dengan Perusahaan yang memberikan Jasa Konsultan dilakukan secara adil dan seimbang sehingga menghasilkan kontrak kerja yang sesuai dengan harapan antara kedua belah pihak.Kata Kunci: Perlindungan Hukum, Terhadap, Konsultan, Dalam, Kontrak Kerja.